FAURE, JMB Inventory of documents - FAURE, JMB (ARCA, 2018)
Principal Grey College and Steynrust; Inspector of Education; Pamphlet and programme pertaining to Afrikanerbond (March 1899).
COVERAGE 2 files; 0.10 metre
Keywords: FAURE, JMB; Afrikanerbond